The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10886-009-9660-2
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Component Female-Produced Pheromone of the Spider Pholcus beijingensis

Abstract: Chemical signaling plays an important role in spider sexual communication, yet the chemistry of spider sex pheromones remains poorly understood. Unlike insects and mammals, the identification of spider pheromones has seldom been attempted, and no multicomponent pheromones have been found. Empty webs of sexually receptive females of Pholcus beijingensis were more attractive to male conspecifics as compared to webs of sexually unreceptive females or to mature males. Coincidently, chemical analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2010
2010
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
1
26
0
2
Order By: Relevance
“…their palps at the last phase of the courting procedure will the females turn from passive to active, which leads directly to copulation (Xiao et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…their palps at the last phase of the courting procedure will the females turn from passive to active, which leads directly to copulation (Xiao et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Males abandon their webs after their last moult to search for potential mates while the females wait on their webs for males (Chen & Li 2005). We have demonstrated that a combination of (E,E )-farnesyl acetate and hexadecyl acetate acts as a female-produced sex pheromone in this species (Xiao et al 2009). The mate-searching males (MMs) can locate potential mates based on the sex pheromone associated with the female's silk.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Most studies have reported polar solvents as more suitable (Gaskett 2007), and in fact the two characterized contact pheromones associated with female web threads from the linyphiid, Linyphia tringularis (Schulz and Toft 1993), and the ctenid, Cupiennius salei (Papke et al 2000), are both polar compounds bearing free hydroxyl and carboxyl groups, and therefore readily soluble in methanol or water. Nonetheless, non-polar to moderately polar fatty acid and methyl ester pheromones also have been described; cuticle and web contact pheromones in Tegenaria atrica (Agelenidae) (Prouvost et al 1999), the female-emitted volatile (8-methylnonan-2-on) from A. aperta (Papke et al 2001), and (E,E)-farnesyl acetate and hexadecyl acetate associated with the web of Pholcus beijingensis females (Pholcidae) (Xiao et al 2009). …”
Section: Introductionmentioning
confidence: 99%